Bleeding Risk Related to Upper Gastrointestinal Endoscopic Biopsy in Patients Receiving Antithrombotic Therapy: A Multicenter Prospective Observational Study - Takafumi Yuki, MD, PhD; Shunji Ishihara, MD, PhD; Kazuo Yashima, MD, PhD; Koichiro Kawaguchi, MD, PhD; Hirofumi Fujishiro, MD, PhD; Youichi Miyaoka, MD, PhD; Mika Yuki, MD, PhD; Yoshinori Kushiyama, MD, PhD; Akiko Yasugi, MD, PhD; Michiko Shabana, MD, PhD; Koichirou Furuta, MD, PhD; Kiwamu Tanaka, MD, PhD; et al. (Elsevier, 2017)
Background: Although antithrombotic agents are widely used for cardiac and cerebrovascular disease prevention, they increase the risk of gastrointestinal (GI) bleeding. Objective: To examine GI bleeding risk in association with an esophagogastroduodenoscopy (EGD) biopsy performed in patients without cessation of antithrombotic therapy. Methods: This study was prospectively conducted at 14 centers. EGD biopsies were performed in patients receiving antithrombotic agents without cessation, as well as age- and sex-matched controls not receiving antithrombotic therapy. Patients treated with warfarin before the biopsy had a prothrombin time-international normalized ratio level <3.0. The proportion of GI bleeding events was compared between the groups. Results: The patient group (n = 277) underwent a total of 560 biopsies while continuing antithrombotic therapy, of whom 24 were receiving multiple antiplatelet drugs, and 9 were receiving both antiplatelet and anticoagulant agents. The control patients (n = 263) underwent 557 biopsies. The upper-GI bleeding rate within 30 days after the EGD biopsy did not increase in patients without cessation of antithrombotic treatment, regardless of receiving single or multiple antithrombotic agents. Conclusions: We found no significant increase in upper-GI bleeding risk following an EGD biopsy in patients taking antithrombotic agents, suggesting its safety without the need for antithrombotic treatment interruption.